Intentions Into Actions: Norms as Mechanisms Linking Macro- and Micro-Levels. (September 2016) - Brinton, Mary C.
This article addresses the emergence of "lowest-low" fertility in some countries, primarily in Southern Europe and East Asia, and poses the question of why we find such large differences in birth rates across postindustrial societies. A set of macro–micro mechanisms are identified, which are examined empirically using comparative data for seven countries from the Gender and Generations Survey. Social norms, and in particular social norms related to gender roles, are at the center of the analysis as a mechanism that conditions the translation of intentions into behavior. Societies that discourage gender equity in the private sphere of the household tend to be characterized by a strong breadwinner ideology. In these societies, the valorization of women's role as household manager and mother is mirrored by the valorization of men's role as breadwinner for the household. In these societies, there is a strong norm that a young man should be able to support a family prior to getting married and becoming a parent, that is, that males should prove themselves to be adequate breadwinners. When combined with changing structural conditions, such as high unemployment rates, prolonged periods of education, and increasingly insecure terms of employment in flexible labor markets, this norm will lead to declining birth rates. Hence, norms work as a mechanism that filters the effect of structural conditions so that structural constraints on fertility, such as limited labor market opportunities for young men, will affect fertility outcomes via the mechanism of gender-role norms.